Validation of a novel medical device (Chloe SED®) for the administration of analgesia during manual vacuum aspiration: a randomized controlled non-inferiority pilot study - Ramanathan, Aparna; Samenjo, Karlheinz Tondo; Bailey, Robert C.; Imbamba, Javan; Odenyo, Stella; Koksal, Erin; Diehl, Jan Carel; Omoto, Jackton; Gwer, Stephen (Frontiers in Pain Research, 2024)
IntroductionMillions of women worldwide annually undergo manual vacuum aspiration (MVA) with no pain medication, which is a violation of their basic human dignity. We designed a novel device (Chloe SED®) to administer paracervical block (PCB) during MVA in countries where pain medication is not typically given due to the high cost of the necessary tools.MethodsWe conducted a single-blinded, randomized controlled non-inferiority trial including 61 patients at two hospitals in Kisumu, Kenya, to validate Chloe SED® for administration of PCB during MVA. PCB administered with Chloe SED® was compared to PCB administered with a standard spinal needle. Patients requiring MVA were block randomized in blocks of six, each provider completing six PCBs—three with the Chloe SED® and three with the standard spinal needle. The trial was registered with the Kenya Pharmacy and Poisons Board, ECCT/19/03/01 (https://ctr.pharmacyboardkenya.org/applications/index/protocol_no:RUNDVC8xOS8wMy8wMQ__/filter:/investigator:/sites:/pages:5/start_date:/end_date:/disease_condition:/users:/ercs:/stages). An intention-to-treat analysis was completed. The primary outcome was the non-inferiority of the pain score during uterine evacuation with a non-inferiority margin of 2 points on an 11-point numerical rating scale. Secondary outcomes included the non-inferiority of the pain score at four other time points and patient satisfaction.ResultsChloe SED® showed non-inferiority of the primary outcome with a mean pain score during evacuation of 3.8 [90% confidence interval (CI): 3.1–4.6] compared with the spinal needle at 4.1 (90% CI: 3.5–4.7). Non-inferiority of the pain score was shown at all time points. Most patients expressed a desire for the continued use of the device to administer PCB for MVA. No adverse events were noted.ConclusionIn summary, the Chloe SED® appears non-inferior to the spinal needle and desirable for the administration of PCB during MVA.